PELANGGARAN NORMA ADAT MINANGKABAU PADA MASYARAKAT NAGORI PANGEAN KABUPATEN KUANTAN SINGINGI (Studi Kasus Perkawinan Sesuku) - Novita Sriningsih; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Marriage is a relationship between a man and a woman who is legally recognized as a husband and wife with the desire to form a happy and eternal household based on the provisions of the Almighty God. In the Pangean people they carry customs that are not the same as those of most marriages and this difference creates a contradiction between the ulama and adat leaders, which strictly prohibits the occurrence of inter-ethnic marriage. There are 3 custom marriage systems, namely Exogamy, Endogamy and Eleuropogamy. The pangean community in Exogami, where a man is prohibited from marrying a woman who is of the same tribe with him. Inter-ethnic marriages are not prohibited in the Qur'an, nor is there any disadvantage in the hadiths that are prohibited according to the customs in the Pangean community. The research method used in this research is field research immediately descending the community so as to obtain clear information and information gathering techniques in the form of interviews and documentation. Based on the analysis of traditional law, it is stated that the prohibition of inter-ethnic marriage is not prohibited in Islam, in other words, the law of tribal marriage is permissible (mubah). However, in the customary law, marriage of the same ethnicity is prohibited if it is carried out including things that are not good for the family and offspring. Because if there is someone who violates the marriage of his tribe, his family life will not be happy / destitute and his offspring will experience a low IQ deficiency, so Ninik Mamak strictly prohibits his nephews from marrying according to his tribe. Keywords: Customary Norms, Ethnic Marriage, Customary Violation, Minangkabau Customs.